Моделювання режимів роботи двомашинного асинхронного агрегата у трифазній системі координат - Lutso, Valeriy V.; Silvestrov, Anton M.; Spinul, Lyudmila Yu. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The development of experimental prototypes of new types of electric machines as well as searching for them the most effective application areas demands the profound theoretical research. An availability of an adequate mathematical model allows to predict possible errors in operating of upcoming prototypes during the design stage. The mathematical model of two-machine induction motor with the rotary inductor [1] in three-phase coordinate system is given in the article. Models of primary and secondary machines are divided into two structural units. An influence of a rotary inductor on the movement of a rotor is described in the model of the secondary machine, as well as the connection with the primary machine is provided through parameters of torque and rotating speed. Transient response plots are obtained for a two-machine induction motor operating under no load and under nominal load, as well as for the case when only the secondary machine is operating. Based on the plots, the different variants of starting of various motor parts are analyzed. The structure diagram of the model built in MatLab programming environment clearly shows the connection between the primary and secondary machines.